Sistem Informasi Inventory Dan Penjualan Pada Toko Komputer Go_It Berbasis Web Dengan Teknologi Single Page Application (SPA) - Sanjaya, Putut; , Bana Handaga, S.T.,M.T.,P.h.D (2017)
All this time, the inventory and selling system in Go_iT computer store is conventionally carried out. Thus, it result in difficulties and inaccuracy of calculating both the total amounts of items and the price. To ease the data processing, it need a building of computerized item selling information system. With the compurized inventory and selling system, the data produced will be more accelerated and accurate. This research aims at designing an inventory and selling system which is computerized, so that it can ease the operational activities of the store. Stage in the completion of this research consists of need analysis, system design, implementation, system test, and system application. This application is made by using PHP programming language and mysql database. Based on the questionnaires distributed to the respondents, it is found that 85% of the respondents state that the performance of the website is fast and responsive, and 80% of them state that the system can ease the making of the income report and invoice quickly. The final result of the system which has been made is an inventory and store selling system which can proced the item data such as item selling management, invoice making, and income report making. With the catalogue in the store's website, it can ease the costumers to see the stocks available without coming to the store. Besides, the use of single page application technology will also help the website's performance in order to make it faster and more responsive.